2011
DOI: 10.1093/cvr/cvr247
|View full text |Cite
|
Sign up to set email alerts
|

Serine-910 phosphorylation of focal adhesion kinase is critical for sarcomere reorganization in cardiomyocyte hypertrophy

Abstract: FAK undergoes S910 phosphorylation via PKCδ and Src-dependent pathways that are important for cell spreading and sarcomere reorganization. Reduced FAK-S910 phosphorylation may contribute to sarcomere disorganization in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
0
32
1
Order By: Relevance
“…However, the rapid turnover of focal adhesion components plays a crucial role in cellular differentiation and migration during cardiac development [18,89,30,23,24], and may also be an important regulatory factor during new sarcomere addition in response to hypertrophic stimuli [47,10]. Using fluorescence recovery after photobleaching (FRAP) and mathematical modeling, Ingber and colleagues [42] showed that various components of the focal adhesion complex display residence times that vary from as little as 1 sec for vinculin, and up to 111 sec for talin.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the rapid turnover of focal adhesion components plays a crucial role in cellular differentiation and migration during cardiac development [18,89,30,23,24], and may also be an important regulatory factor during new sarcomere addition in response to hypertrophic stimuli [47,10]. Using fluorescence recovery after photobleaching (FRAP) and mathematical modeling, Ingber and colleagues [42] showed that various components of the focal adhesion complex display residence times that vary from as little as 1 sec for vinculin, and up to 111 sec for talin.…”
Section: Introductionmentioning
confidence: 99%
“…Sanger and co-workers [86] had previously observed a similar dynamic range of exchange between costamere/Z-disc proteins and the cytoplasm of spreading skeletal muscle myotubes. Using FRAP, we subsequently demonstrated that the phosphorylation of FAK, a critical component of the signaling layer of cardiomyocyte focal adhesions, regulates the stability of paxillin within cardiomyocyte focal adhesions, and ultimately controls the rate of cell spreading and myofibrillar organization of cultured cardiomyocytes in response to both static stretch, and the hypertrophic agonist endothelin-1 [10]. Thus, the dynamic nature of cytoskeletal assembly and disassembly within focal adhesion complexes appears critical during the response of cultured cardiomyocytes to neurohormonal and mechanical stimuli.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations